Respuesta :

Mibo

Answer:

Step-by-step explanation:

Putting values of x in equation

Y = 4(-3) - 4

= - 12 - 4 = - 16

Y = 4(-2) - 4

= - 8 - 4 = - 12

Y = 4(-1) - 4

= - 4 - 4 = - 8

Y = 4(0) - 4

= 0 - 4 = - 4

Y = 4(1) - 4

= 4 - 4 = 0

Y = 4(2) - 4

= 8 - 4 = 4

Y = 4(3) - 4

= 12 - 4 = 8

Answer:

Step-by-step explanation:

Putting values of x in equation

Y = 4(-3) - 4

= - 12 - 4 = - 16

Y = 4(-2) - 4

= - 8 - 4 = - 12

Y = 4(-1) - 4

= - 4 - 4 = - 8

Y = 4(0) - 4

= 0 - 4 = - 4

Y = 4(1) - 4

= 4 - 4 = 0

Y = 4(2) - 4

= 8 - 4 = 4

Y = 4(3) - 4

= 12 - 4 = 8

Step-by-step explanation:

ACCESS MORE